Ez-stopper / Mohd Azuan Tukiar ... [et al.] - Tukiar, Mohd Azuan; Ahmad, Mohd Munir; Sidek, Mohd Azrul; Leiahs, Lesairuamin; Ibrahim, Siti Zalipah; Din, Mazli; Jamil, Mohd Yazid (Universiti Teknologi MARA, Kedah, 2019)
Stop valve is the most important component of the piping system. It has two main functions which are to control the flow rate and to stop the flow of water. This project is about the innovation of a stop valve known as Ez - Stopper. It is created to replace the original stop valve function which is often damaged in the bathroom of Kolej Intan, UiTM Penang Branch. Ez - Stopper has gone through several stages of the innovation process and has also undergone several series of tests to ensure the effectiveness of the functionality as well as the durability of the tool. As a result of the Ez - Stopper innovation, several positive impacts have been achieved, namely: (1) Time saving - Save the repair process before the project from 8 hours to 1 hour and no more spare parts booking process for repairs up to 6 - 8 weeks (2 ) Cost of saving repair - Save cost of repair up to RM12,254 (94%) (3) Spare parts savings - Spare parts savings up to RM3,522 (98%). In terms of potential of commercialization, there are two contractor companies interested in using Ez - Stopper if it is commercialized to the local market due to the low cost and suitable for replacing the original stop valve. Ez - Stopper has also been registered for patent purposes at MyIPO (Registration No: PI2017500024) and registered at Research Business Unit (RIBU). This innovation project is also in line with the mission and vision of the College & Non-Resident Management Unit which provides conducive facilities to college students.